Onherhaalbaar, onontdoenbaar: Die doop as simbool van eenheid in die kerk - Oudtshoorn, David A. van (HTS teologiese studies, 2013)
Irrevocably singular: Baptism as a symbol of unity in the church. In this article I conduct a phenomenological analysis of the concept ‘one baptism’ in Ephesians 4:4−6. Such an analysis seeks to reveal the essence of a particular concept by bracketing out the theological and ideological presuppositions usually associated with it. The essential concept is then expanded by linking it to the terms most closely surrounding it in the text. A critical theological reflection on the expanded concept shows that ‘one baptism’ refers to an event by which believers are inducted, once and for all, into the church as the one body of the one Lord, Jesus Christ. The church exists through the presence of the one Spirit who binds believers in an unbreakable bond of love to God and to each other. Because baptism can never be undone or repeated, any liturgical act depicted as a ‘re-baptism’ is, by definition, impossible. This means that churches that baptise the children of believing parents are able to accommodate requests from people who, having been baptised as an infant, in later life wish to celebrate and testify to some significant milestone in their spiritual journey by means of an official church ritual. Such ritualised testimonies, however, refer to the existential lifeworld of believers (their repentance, confession of faith etc.) and are distinct from baptism that refers to the singular eschatological work of Christ and thus cannot be repeated. The church should, however, take pastoral care to ensure that people do not substitute their own spiritual experiences for the reality of salvation that is founded on the singular act of God, for us once and for all in Christ, to which baptism irrevocably refers.